Labour's National Campaign for Spain: Royal Albert Hall Sub-Committee: agenda (annotated)
C03-0013-001 £25 £35 - 5000 200,000 Handbills (Post 5000) LABOUR'S NATIONAL CAMPAIGN FOR SPAIN. Curwen (Press Assocn) MEETING of Royal Albert Hall Sub-committee, House of Commons, Monday November 8th at 4 p.m. to make arrangements for the Royal Albert Hall Demonstration - December 19th. (Sunday) Forward Manchester Guardian [ ] New Statesman Cooperative [ ] AGENDA. (1) Printing. - London Labour Party (2) Tickets - number to be printed and prices. (3) Press Advertising. - Herald - Star - News Chronicle - Reynolds Newspaper - London News Bulletin (4) Circularisation of Labour Parties and kindred organisations:- (a) re: tickets. (b) re: organisation of immediate collections. T.U.C. & Women's section (5) Allocation of platform tickets. (6) Stewards. (Agents) + Literature Stewards) Leonard Castle (7) Music (organ or choir.) - Loud Speakers (10 guineas) Literature - 6.30 pm 6.45 to 7 pm Organ - [7.45] Choir at 7 pm Choral concert [7.30 8 pm] Speaking - 7.15 - 7.30 pm Address before Concert Collection Ch. union after collection 292C/946/3/13